Probabilistic methods applied to fluctuating systems - Corker, Lloyd A (Department of Physics, 2014)
In this work the hierarchical structure of three diverse stochastic systems is studied by investigating the probability densities of their scale-dependent measures across various scales. In the first system studied, velocity increments are used to investigate the order of complexity and disorder of wind turbulence. The second system investigates the disorders of skeletal muscles and the nervous system by considering the fluctuation of electric potentials of skeletal muscles. The last system studied is a non-physical system where price increments are used to classify the financial markets in terms of predictability of price changes and market efficiency. In all three stochastic systems a Fokker-Planck equation is used to describe how the scale-dependent measure is correlated across nested scales.